1951
DOI: 10.1111/j.1096-3642.1951.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

The feeding habits of certain chironomid larvae (subfamily Tendipedinae).

Abstract: SUMMARY The nature of the food and the feeding mechanisms of various chironomid larvae with different modes of life have been studied by observing their feeding behaviour in the laboratory and their gut contents in nature and under experimental conditions. Of Tendipes (=Chironomus) larvae, only T. plumosus employs a filter‐feeding mechanism with a salivary net spun across the lumen of its tube anterior to the body. Other larvae of the plumosus‐group (e. g. T. dorsalis), although identical in larval morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Chironomid larvae are omnivorous, but predominantly detrital feeders (Hart & Lovvorn, 2003), and there is no evidence in the Zemeno tufa that the Phormidium shrubs surrounding the chironomid larval tubes have been eaten. Some types of chironomid larvae feed by smearing the tops of their tubes with a layer of ‘salivary secretion’, later dragging the mucilage and adhered detritus with them for consumption (Walshe, 1951; Oliver, 1971). Furthermore, the tubes in which many chironomid larval species live are held together by such secretions (Walshe, 1951; Oliver, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Chironomid larvae are omnivorous, but predominantly detrital feeders (Hart & Lovvorn, 2003), and there is no evidence in the Zemeno tufa that the Phormidium shrubs surrounding the chironomid larval tubes have been eaten. Some types of chironomid larvae feed by smearing the tops of their tubes with a layer of ‘salivary secretion’, later dragging the mucilage and adhered detritus with them for consumption (Walshe, 1951; Oliver, 1971). Furthermore, the tubes in which many chironomid larval species live are held together by such secretions (Walshe, 1951; Oliver, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies of the mesh of Chironomus plumosus nets revealed an effective pore size of 12 to 17 µm (Walshe 1947(Walshe , 1951, which is too large for bacteria. Thus, unless the pelagic MOB are associated with flocs, it is unlikely that such a source contributes substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some Chironomus species filter particles from water overlying sediments (Walshe, 1951), whereas others consume deposited sediment particles (J onasson, 1972). Thus, some Chironomus species filter particles from water overlying sediments (Walshe, 1951), whereas others consume deposited sediment particles (J onasson, 1972).…”
Section: Introductionmentioning
confidence: 99%